Pengaruh Profesionalisme dan Kedisiplinan Terhadap Kinerja Guru Di SMK Kelautan Sunan Drajat Kecamatan Paciran Kabupaten Lamongan - Asykuri, Moh. (MADINAH, 2015)
Professionalism of a teacher is very influential on improving the quality of education success to learners, because the professionalism of teachers is a device of ability that must be owned by a teacher so that he can carry out his teaching duties properly and successfully, therefore to become a professional teacher who has accountability in carry out pengelolahan learning requires determination and a strong desire in each prospective teacher or teacher to make it happen. In addition, teachers are required for discipline in the profession of work as educators. According Nitisemito (1986: 1990) states the problem of work discipline is a matter that needs to be considered, because with the discipline, can be affected effectiveness and efficiency in achieving educational goals. This means that Discipline is one of the success factors of organizational goals in the education environment of SMK Sunan Drajat. An organization must have a purpose, so that the organization's wheels run smoothly and directed.